Pengaruh Lingkungan, Fasilitas, dan Insentif Terhadap Motivasi dan Kinerja Karyawan PT PAL Indonesia Divisi Rekayasa Umum - Shintya Vira Istiqfari; Bambang Syairudin; M. Yusak Anshori (UNUSA Press, 2017)
PT PAL Indonesia is one of the largest company engaged in the maritime field, the existence of competition at national and international very tight then the company should always have a good strategy in the field of technology and human resources, so in this study focused on the performance of employees in the engineering division general. The study is aim to determine the effect of environment, facilities, incentives and motivation to employees performance in PT PAL Indonesia general engineering division. Using the technique of analysis Structural Equation Modelling (SEM) - Partial Least Square (PLS). The result of this study is performance variable explained by environmental, facilities, incentives and motivation only 64,4%, while 35,6% explained by other variables, significant effect on the environment of motivation with the value of t statistic 3,412, significant effect on environment of performance variable with the value of t statistic 1,97, and significant effect on motivation of performance variable with the value of t statistic 1,82.